A dual-conductive network structure absorbing electromagnetic shielding composite material and a preparation method thereof

CN123021630APending Publication Date: 2026-10-30ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510546448.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0027](1)本发明电磁屏蔽复合材料的构型具有更大的自由度。高、低导电电磁屏蔽层与多孔结构层之间的制备方式相互独立,不同高、低导电磁屏蔽层和多孔结构层可进行自由组合,从而便于调节电磁屏蔽材料的反射或吸收主导特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123021630A_ABST
    Figure CN123021630A_ABST
Patent Text Reader

Abstract

The application relates to the field of electromagnetic shielding materials, and discloses a double-conductive-network-structure absorption type electromagnetic shielding composite material and a preparation method thereof. The absorption type electromagnetic shielding composite material comprises a porous structure layer and low-conductive electromagnetic shielding layers and high-conductive electromagnetic shielding layers arranged on two surfaces of the porous structure layer; the low-conductive electromagnetic shielding layers are used to realize impedance matching, thereby absorbing more electromagnetic waves and obtaining a higher absorption coefficient; meanwhile, the high-conductive electromagnetic shielding layers are used to provide higher shielding efficiency and construct a double-conductive-network structure. Specifically, the low-conductive electromagnetic shielding layers in the double-conductive-network structure play an absorption role and help to improve impedance matching between the shielding material and free space, and the high-conductive electromagnetic shielding layers jointly form an electromagnetic loss path of 'absorption-reflection-reabsorption' with a reflection layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electromagnetic shielding materials, and in particular to a dual-conductive network structure absorption-type electromagnetic shielding composite material and its preparation method. Background Technology

[0002] Electromagnetic radiation pollution has become one of the most significant environmental pollution problems in contemporary society. With the widespread use of portable electronic devices, 5G and future 6G wireless communication technologies inevitably generate large amounts of electromagnetic radiation at different frequencies, leading to its accumulation in space. This not only interferes with the normal operation of electronic devices and has negative impacts on the environment, but long-term exposure to strong electromagnetic radiation can also cause lesions in some tissues, seriously threatening human health. Therefore, developing novel high-performance electromagnetic shielding materials to promote the absorption and dissipation of electromagnetic radiation has become a key research focus.

[0003] Currently, conductive polymer composites, consisting of a polymer matrix and conductive fillers, have made significant progress in the preparation of electromagnetic shielding materials due to their advantages such as light weight, ease of processing, good flexibility, and corrosion resistance. However, because polymers themselves have low electrical conductivity, a large amount of conductive filler is often needed to fill the polymer matrix to form a conductive network in order to improve electromagnetic shielding capabilities. However, excessive conductive filler can exacerbate the impedance mismatch between the material and air, resulting in high electromagnetic wave reflectivity and causing serious secondary pollution.

[0004] Therefore, how to achieve efficient electromagnetic shielding and high absorption performance while ensuring good impedance matching between the material and air has become a hot topic in current electromagnetic shielding material research. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a dual-conductive network structure absorptive electromagnetic shielding composite material and its preparation method. The absorptive electromagnetic shielding composite material of this invention comprises a porous structural layer and a low-conductivity electromagnetic shielding layer and a high-conductivity electromagnetic shielding layer disposed on its two surfaces. This invention achieves impedance matching through the low-conductivity electromagnetic shielding layer, thereby absorbing more electromagnetic waves and obtaining a higher absorption coefficient. Simultaneously, it utilizes the high-conductivity electromagnetic shielding layer to provide higher shielding effectiveness, thus constructing a dual-conductive network structure. Specifically, the low-conductivity electromagnetic shielding layer in the dual-conductive network structure plays an absorption role, helping to improve the impedance matching between the shielding material and free space, while the high-conductivity electromagnetic shielding layer, together with the reflective layer, forms an electromagnetic loss path of "absorption-reflection-reabsorption".

[0006] The specific technical solution of this invention is as follows:

[0007] First, the present invention provides a dual conductive network structure absorption electromagnetic shielding composite material, which includes at least one layer of stacked porous structure layer, and at least one low conductive electromagnetic shielding layer and at least one high conductive electromagnetic shielding layer respectively disposed on the two surfaces of the stacked porous structure layer.

[0008] The porous structure layer is one or more of nanofiber membrane, melamine foam, and EPE foam; the low conductivity electromagnetic shielding layer is a nanofiber membrane containing carbon nanoparticle conductive filler; and the high conductivity electromagnetic shielding layer is a nanofiber membrane containing nano-silver.

[0009] In this invention, high- and low-conductivity electromagnetic shielding layers form a conductive network with a dual-conductivity structure, constructing an electromagnetic shielding mechanism of "absorption-reflection-reabsorption" within the thin film. The low-conductivity electromagnetic shielding layer improves impedance matching and reduces microwave reflection at the film surface, while the high-conductivity electromagnetic shielding layer acts as a shielding reflection layer, providing excellent electromagnetic shielding performance. Therefore, the electromagnetic shielding composite material prepared by this invention not only has high absorption efficiency for electromagnetic waves but also excellent electromagnetic shielding performance. By adjusting the high- and low-conductivity electromagnetic shielding composite materials or changing the thickness of the porous structure layer, this invention can prepare shielding materials with a shielding performance as high as 72.79 dB and an absorption coefficient of 0.95. This material not only possesses excellent electromagnetic shielding effectiveness but also meets the requirements of being lightweight, flexible, and having high shielding performance, showing broad application prospects, especially suitable for human protection, communication electronics, aerospace, and high-precision fields.

[0010] Preferably, the electromagnetic shielding effectiveness (SE) of the low-conductivity electromagnetic shielding layer is... T The range is less than 20 dB; the electromagnetic shielding effectiveness (SE) of the highly conductive electromagnetic shielding layer is... T The range is greater than 20dB.

[0011] Preferably, the total thickness of the porous structure layer is 0.2-10 mm.

[0012] Secondly, this invention provides a method for preparing a dual-conductive network structure absorption-type electromagnetic shielding composite material, which includes the following steps:

[0013] S1. Electrospinning is used to prepare nanofiber membranes from polymer spinning solutions.

[0014] S2. The nanofiber membrane obtained in S1 is placed in an alkaline solution containing dopamine hydrochloride, stirred, washed and dried, and then immersed in silver nitrate solution. The pH value is adjusted with ammonia water to make the solution change from brown to transparent. Glucose is added, stirred, washed with water, and dried to obtain a highly conductive electromagnetic shielding layer.

[0015] S3. One or more of the nanofiber membrane, melamine foam and EPE foam obtained in S1 are hot-pressed to form a stacked porous structure layer.

[0016] S4. The nanofiber membrane obtained in S1 is first soaked in sodium polyacrylate solution, and then soaked in polyethyleneimine solution a second time. Then, the nanofiber membrane is placed in a dispersion containing carbon nano-conductive filler for adsorption, washing, and drying to obtain a low-conductivity electromagnetic shielding layer.

[0017] S5. At least one highly conductive electromagnetic shielding layer, a stacked porous structure layer, and at least one low conductive electromagnetic shielding layer are hot-pressed together.

[0018] Preferably, in S1, the polymer is selected from at least one of polyamide, polyurethane elastomer, polyacrylonitrile, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyimide, epoxy resin, polylactic acid, polymethyl methacrylate, cellulose, cellulose acetate, chitosan, gelatin and silk protein; more preferably, thermoplastic polyurethane elastomer.

[0019] Preferably, in S1, the thickness of the single-layer nanofiber membrane is 0.05-1 mm.

[0020] Preferably, in S2, the content of dopamine hydrochloride in the alkaline solution is 1-3 g / L, and the pH is 8-9; the concentration of silver nitrate in the silver nitrate solution is 6-10 g / L; and the amount of glucose used is 1.8-2.2 times the mass of silver nitrate.

[0021] Preferably, in S3, one or more of the nanofiber membrane, melamine foam, and EPE foam are bonded together by hot-pressing a TPU hot melt mesh film.

[0022] Preferably, in step S4, the concentration of sodium polyacrylate in the sodium polyacrylate solution is 0.8-1.2 wt%, the pH is 1-2, and the first soaking time is 3-10 min; the concentration of polyethyleneimine in the polyethyleneimine solution is 0.3-0.7 wt%, the pH is 8.5-9.5, and the second soaking time is 3-10 min.

[0023] Preferably, in step S4, the adsorption time is 15-300 min.

[0024] Preferably, in S4, the carbon nanotube conductive filler is selected from at least one of carbon black, graphene, carbon nanotubes and carbon nanosheets; more preferably, carbon nanotubes are used.

[0025] Preferably, in step S4, the content of carbon nanotube conductive filler in the dispersion is 10-30 g / L.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] (1) The configuration of the electromagnetic shielding composite material of the present invention has greater freedom. The preparation methods of the high and low conductivity electromagnetic shielding layers and the porous structure layer are independent of each other, and different high and low conductivity electromagnetic shielding layers and porous structure layers can be freely combined, thereby facilitating the adjustment of the dominant reflection or absorption characteristics of the electromagnetic shielding material.

[0028] (2) By preparing an electromagnetic shielding composite material with a dual conductive network structure, the present invention can significantly improve the conductivity and electromagnetic shielding performance of the material while effectively reducing electromagnetic wave reflection, thereby achieving the goal of low reflection, high conductivity and high shielding performance.

[0029] (3) By adjusting the shielding effectiveness of the low-conductivity electromagnetic shielding layer, the absorption coefficient of the electromagnetic shielding material can be effectively adjusted. In addition, by changing the thickness of the porous structure layer, the absorption coefficient of the electromagnetic shielding material can also be further adjusted. By improving the shielding effectiveness of the high-conductivity electromagnetic shielding layer, the total shielding effectiveness of the material can be effectively improved, and the effect on the absorption coefficient is small.

[0030] (4) Compared with the traditional shielding material preparation method, the present invention has a simpler and more feasible preparation process, and the structural design is more novel, which improves the application flexibility of the material. Attached Figure Description

[0031] Figure 1 This is a scanning electron microscope image of the nanofiber membrane prepared in Example 1 of the present invention;

[0032] Figure 2 This is a scanning electron microscope image of carbon nanotubes adsorbed by a nanofiber membrane in Example 1 of the present invention;

[0033] Figure 3 This is a scanning electron microscope image of silver nanoparticles deposited in situ on a nanofiber membrane in Example 1 of the present invention;

[0034] Figure 4 The following are digital photographs of Embodiment 1 of the present invention: (a) a digital photograph of a high-conductivity electromagnetic shielding layer (TPU / PDA / AgNPs), (b) a digital photograph of a low-conductivity electromagnetic shielding layer (TPU / SDS / CNTs), and (c) a digital image of the composite film thickness.

[0035] Figure 5 The graph shows the total shielding effectiveness and average power coefficient of the AgNPs-x / TPU-4 / CNTs-4 composite film prepared in Example 1 of this invention, with the same porous structure layer thickness and low conductivity electromagnetic shielding layer, and different high conductivity electromagnetic shielding layers.

[0036] Figure 6The graph shows the total shielding effectiveness and average power coefficient of the AgNPs-70 / TPU-y / CNTs-4 composite film prepared in Example 2 of this invention, with the same high and low conductivity electromagnetic shielding layers and different porous structure layer thicknesses.

[0037] Figure 7 The graph shows the total shielding effectiveness and average power coefficient of the AgNPs-70 / TPU-4 / CNTs-z composite film prepared in Example 3 of this invention, with the same thickness and high conductivity electromagnetic shielding layer, and different low conductivity electromagnetic shielding layers.

[0038] Figure 8 This is a comparison chart of the total shielding effectiveness and absorption coefficient of the AgNPs-70 / MF-n / CNTs-4 composite material prepared in Example 4 of the present invention. Detailed Implementation

[0039] The following examples use carbon nanotubes and silver nanoparticles as conductive fillers and thermoplastic polyurethane elastomer (TPU) as nanofiber membrane materials. They are only used to illustrate the implementation of the present invention and do not limit the scope of the present invention in any way.

[0040] Example 1: Preparation of a high-absorption electromagnetic shielding composite film AgNPs-x / TPU-4 / CNTs-4 with a dual conductive network structure

[0041] Step 1, Preparation of TPU Nanofiber Membrane: Weigh 15g of thermoplastic polyurethane elastomer (TPU), 42.5g of N,N-dimethylformamide, and 42.5g of tetrahydrofuran. Mix the three components in a beaker and magnetically stir for 24h to obtain the TPU spinning solution. Prepare a 0.2mm thick TPU nanofiber membrane using electrospinning technology. The spinning parameters are: voltage 20kV, spinning distance 16cm, and spinning speed 2mL / h. Its microstructure is shown below. Figure 1 As shown, from Figure 1 As can be seen, the individual fibers of the TPU nanofiber membrane are smooth and flat.

[0042] Step 2, Preparation of the High Conductivity Electromagnetic Shielding Layer: 0.2g of dopamine hydrochloride was dissolved in 100mL of deionized water, and the pH was adjusted to 8.5 with ammonia. The TPU nanofiber membrane was then placed in this solution for modification, stirred at room temperature for 24h, followed by ultrasonic cleaning with deionized water multiple times, and baking at 50℃ for 2h. 0.8g of silver nitrate was dissolved in 100mL of deionized water, and ammonia was added to change the solution from brown to transparent. Then, 1.6g of glucose was added, and the modified TPU nanofiber membrane was placed in the solution. The mixture was stirred for 30, 60, and 120min, respectively, to obtain composite films with shielding effectiveness of 20, 50, and 70dB, named AgNPs-x (x = 20, 50, and 70), and their microstructure is shown below. Figure 3 As shown, from Figure 3It can be seen that the silver nanoparticles are tightly coated on each TPU nanofiber.

[0043] Step 3, Preparation of porous structure layer: The TPU nanofiber membrane is processed by hot pressing to prepare a film with a thickness of 4 mm, named TPU-4.

[0044] Step 4, Preparation of the low-conductivity electromagnetic shielding layer: Prepare a 0.1 g / L sodium polyacrylate solution and adjust the pH to 1.5 with hydrochloric acid; prepare a 0.5 g / L polyethyleneimine solution and adjust the pH to 9 with hydrochloric acid. Soak the TPU nanofiber membrane in both solutions for 5 min, then wash and dry. Weigh 3 g of carbon nanotubes and 3 g of sodium dodecyl sulfate and add them to 100 mL of deionized water. Disperse them evenly by ultrasonication. Then, place the treated TPU nanofiber membrane in the mixed solution and ultrasonically soak it for 60 min to obtain a composite film with an electromagnetic shielding effectiveness of 4 dB, named CNTs-4. Its microstructure is as follows: Figure 2 As shown, from Figure 2 It can be observed that there are obvious carbon nanotubes on the individual fibers of the composite film.

[0045] Step 5: The AgNPs-x, TPU-4, and CNTs-4 films prepared above are bonded together by hot-pressing with a TPU hot-melt web film at 150℃, finally obtaining a composite film with a dual conductive network structure, named

[0046] AgNPs-x / TPU-4 / CNTs-4, its surface morphology is as follows Figure 4 As shown.

[0047] The shielding performance of AgNPs-x / TPU-4 / CNTs-4 was evaluated using a vector network analyzer, as shown in Table 1. Figure 5 .

[0048] Table 1: Shielding performance of composite films with different high-conductivity electromagnetic shielding layers, while maintaining the thicknesses of the low-conductivity electromagnetic shielding layer and the porous structure layer.

[0049]

[0050] Based on Table 1, the following summary conclusions are drawn:

[0051] When the thicknesses of the low-conductivity electromagnetic shielding layer and the porous structure layer are fixed, the overall shielding effectiveness increases significantly with the increase of the shielding effectiveness of the high-conductivity electromagnetic shielding layer, but the effect on the absorption coefficient is not significant. Therefore, the overall shielding effectiveness can be improved by increasing the shielding effectiveness of the high-conductivity electromagnetic shielding layer, thus producing a high-absorption, low-reflection electromagnetic shielding material.

[0052] Example 2: Preparation of a high-absorption electromagnetic shielding composite film AgNPs-70 / TPU-y / CNTs-4 with a dual conductive network structure

[0053] The composite film AgNPs-70 / TPU-y / CNTs-4 was prepared according to the method of Example 1. The difference is that the composite film AgNPs-70 with a high conductivity electromagnetic shielding layer of 70dB, the composite film CNTs-4 with a low conductivity electromagnetic shielding layer of 4dB, and the film with a porous structure layer thickness of 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, and 8.0 mm were prepared and named TPU-y (y is 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, and 8.0 mm).

[0054] The shielding performance of AgNPs-70 / TPU-y / CNTs-4 was evaluated using a vector network analyzer, as shown in Table 2. Figure 6 The shielding effectiveness was tested using an AV3672 vector network analyzer in the 8.2-12.4 GHz (X-band) frequency range.

[0055] Table 2: Shielding performance of composite films with different porous structure layer thicknesses, using fixed high and low conductivity electromagnetic shielding layers.

[0056]

[0057] Based on Table 2, the following summary conclusions are drawn:

[0058] With fixed high and low conductivity electromagnetic shielding layers, the overall shielding effectiveness did not change significantly with the increase of the porous structure layer thickness. The absorption coefficient first increased and then decreased, reaching a maximum value of 0.95 when the porous structure layer thickness was 4 mm. When the shielding effectiveness of the low conductivity electromagnetic shielding layer was 4 dB and the porous structure layer thickness was 1 mm, the shielding performance of the material was dominated by absorption loss, and the absorption coefficient reached 0.74. A lightweight, flexible electromagnetic shielding material with high absorption and high shielding was successfully prepared.

[0059] Example 3: Preparation of a high-absorption electromagnetic shielding composite film AgNPs-70 / TPU-4 / CNTs-z with a dual conductive network structure

[0060] The composite film AgNPs-70 / TPU-4 / CNTs-z was prepared according to the method in Example 1. The difference lies in the preparation of a composite film with a high conductivity electromagnetic shielding layer of 70dB (AgNPs-70), a porous structure layer of 4mm thickness (TPU-4), and low conductivity electromagnetic shielding layer with shielding effectiveness of 0.3, 2.0, 3.0, 4.0, 6.0, and 10.0dB, respectively. This composite film was named CNTs-z (z = 0.3, 2.0, 3.0, 4.0, 6.0, and 10.0dB).

[0061] The shielding performance of AgNPs-70 / TPU-4 / CNTs-z was evaluated using a vector network analyzer, as shown in Table 3. Figure 7 .

[0062] Table 3: Shielding performance of composite films with different low-conductivity electromagnetic shielding layers, while maintaining the thicknesses of the high-conductivity electromagnetic shielding layer and the porous structure layer.

[0063]

[0064] Based on Table 3, the following summary conclusions are drawn:

[0065] With a fixed thickness of the high-conductivity electromagnetic shielding layer and the porous structure layer, the total shielding effectiveness does not change significantly as the shielding effectiveness of the low-conductivity electromagnetic shielding layer increases. The absorption coefficient first increases and then decreases. When the shielding effectiveness of the low-conductivity electromagnetic shielding layer is 4dB, the absorption coefficient reaches its maximum value (0.95), achieving high absorption and low reflection. As the shielding effectiveness of the low-conductivity electromagnetic shielding layer gradually increases from 4dB, the absorption coefficient shows a gradual decreasing trend.

[0066] Example 4: Preparation of a high-absorption electromagnetic shielding composite material AgNPs-70 / MF-n / CNTs-4 with a dual conductive network structure

[0067] The composite material AgNPs-70 / MF-n / CNTs-4 was prepared according to the method of Example 1. The difference is that a composite film with a high conductivity electromagnetic shielding layer of 70dB, AgNPs-70, and a composite film with a low conductivity electromagnetic shielding layer of 4dB were prepared. The porous structure layer was prepared by cutting melamine foam into different thicknesses and naming them MF-n (n is 2, 3, 4, 5, 6, 8). Finally, AgNPs-70 / MF-n / CNTs-4 with a dual conductive network structure was obtained.

[0068] The electromagnetic shielding performance of the composite film was evaluated using a vector network analyzer, as shown in Table 4 below. Figure 8 .

[0069] Table 4: Electromagnetic shielding performance of electromagnetic shielding layers with the same high and low conductivity at different thicknesses

[0070]

[0071] Based on Table 4, the following summary conclusions are drawn:

[0072] With the same high and low conductivity electromagnetic shielding layers, the overall shielding effectiveness does not change significantly with the increase of the porous structure layer thickness, while the absorption coefficient shows a trend of first increasing and then decreasing. When the shielding effectiveness of the low conductivity electromagnetic shielding layer is 4dB, the shielding effectiveness of the high conductivity electromagnetic shielding layer is 70dB, and the thickness of the intermediate porous structure layer is 4mm, the overall shielding effectiveness reaches 79.75dB, and the absorption coefficient is 0.96, achieving high absorption and high shielding.

[0073] Comparative Example 1

[0074] According to Examples 2 and 3, a composite film with a low conductivity electromagnetic shielding layer shielding effectiveness of 4dB and a film with a porous structure layer thickness of 2mm were prepared and bonded together by hot pressing to obtain the composite film TPU-2 / CNTs-4. The electromagnetic shielding performance of the composite film was then tested using a vector network analyzer.

[0075] Comparative Example 2

[0076] According to Examples 1 and 2, a composite film with a high conductivity electromagnetic shielding layer shielding effectiveness of 70dB and a film with a porous structure layer of 2mm thickness were prepared. They were then bonded together by hot pressing to obtain the composite film AgNPs-70 / TPU-2. The electromagnetic shielding performance of the composite film was then tested using a vector network analyzer.

[0077] Comparative Example 3

[0078] Composite films with a high conductivity electromagnetic shielding layer effectiveness of 70 dB and a low conductivity electromagnetic shielding layer effectiveness of 4 dB were prepared according to Examples 1 and 3. These films were then bonded together by hot pressing to obtain the composite film AgNPs-70 / CNTs-4. The electromagnetic shielding performance of the composite film was then tested using a vector network analyzer.

[0079] Comparative Example 4

[0080] According to Examples 1 and 3, a composite film with a high conductivity electromagnetic shielding layer shielding effectiveness of 70dB and a porous structure layer thickness of 2mm were prepared. AgNWs were sprayed onto a nanofiber membrane with a thickness of 0.2mm to obtain a composite film with a low conductivity electromagnetic shielding layer shielding effectiveness of 15dB. The three were then bonded together by hot pressing to obtain the composite film AgNPs-70 / TPU-4 / AgNWs-15. The electromagnetic shielding performance of the composite film was then tested using a vector network analyzer.

[0081] The shielding performance was evaluated and analyzed, as shown in Table 5 below.

[0082] Table 5: Electromagnetic shielding performance of the composite materials prepared in Examples 2, 4 and comparative examples

[0083]

[0084] Based on Table 5, the following summary conclusions are drawn:

[0085] As can be seen from Table 5, the composite electromagnetic shielding material with a dual conductive network structure obtained by the method of the present invention has higher electromagnetic shielding effectiveness and higher absorption coefficient compared with composite materials with a single high-conductivity electromagnetic shielding layer, a single low-conductivity electromagnetic shielding layer, or no porous structure layer.

[0086] The above description is merely a specific embodiment of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A dual-conductive network structure absorption-type electromagnetic shielding composite material, characterized in that: It includes at least one layer of stacked porous structure layer, and at least one low-conductivity electromagnetic shielding layer and at least one high-conductivity electromagnetic shielding layer respectively disposed on two surfaces of the stacked porous structure layer. The porous structure layer is one or more of nanofiber membrane, melamine foam, and EPE foam; the low conductivity electromagnetic shielding layer is a nanofiber membrane containing carbon nanoparticle conductive filler; and the high conductivity electromagnetic shielding layer is a nanofiber membrane containing nano-silver.

2. The dual-conductive network structure absorption-type electromagnetic shielding composite material as described in claim 1, characterized in that: The electromagnetic shielding effectiveness (SE) of the low-conductivity electromagnetic shielding layer T The range is less than 20 dB; The electromagnetic shielding effectiveness (SE) of the highly conductive electromagnetic shielding layer T The range is greater than 20 dB; The total thickness of the porous structure layer is 0.2-10 mm.

3. A method for preparing a dual-conductive network structure absorption-type electromagnetic shielding composite material as described in claim 1 or 2, characterized in that... Includes the following steps: S1. Electrospinning is used to prepare nanofiber membranes from polymer spinning solutions. S2. The nanofiber membrane obtained in S1 is placed in an alkaline solution containing dopamine hydrochloride, stirred, washed and dried, and then immersed in silver nitrate solution. The pH is adjusted with ammonia water to make the solution change from brown to transparent. Glucose is added, stirred, washed with water, and dried to obtain a highly conductive electromagnetic shielding layer. S3. One or more of the nanofiber membrane, melamine foam and EPE foam obtained in S1 are hot-pressed to form a stacked porous structure layer. S4. The nanofiber membrane obtained in S1 is first soaked in sodium polyacrylate solution, and then soaked in polyethyleneimine solution a second time. Then, the nanofiber membrane is placed in a dispersion containing carbon nano-conductive filler for adsorption, washing, and drying to obtain a low-conductivity electromagnetic shielding layer. S5. At least one highly conductive electromagnetic shielding layer, a stacked porous structure layer, and at least one low conductive electromagnetic shielding layer are hot-pressed together.

4. The preparation method according to claim 3, characterized in that: In S1, the polymer is selected from at least one of polyamide, polyurethane elastomer, polyacrylonitrile, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polyimide, epoxy resin, polylactic acid, polymethyl methacrylate, cellulose, cellulose acetate, chitosan, gelatin, and silk protein.

5. The preparation method according to claim 3 or 4, characterized in that: In S1, the thickness of the single-layer nanofiber membrane is 0.05-1 mm.

6. The preparation method according to claim 3, characterized in that: In S2, The alkaline solution contains 1-3 g / L of dopamine hydrochloride and has a pH of 8-9. The concentration of silver nitrate in the silver nitrate solution is 6-10 g / L; The amount of glucose used is 1.8-2.2 times the mass of silver nitrate.

7. The preparation method according to claim 3, characterized in that: In S3, one or more of the nanofiber membrane, melamine foam and EPE foam are bonded together by hot-pressing TPU hot melt mesh film.

8. The preparation method according to claim 3, characterized in that: In S4, The sodium polyacrylate solution has a sodium polyacrylate concentration of 0.8-1.2 wt% and a pH of 1-2, and the soaking time for each soaking is 3-10 min. The polyethyleneimine solution has a polyethyleneimine concentration of 0.3-0.7 wt% and a pH of 8.5-9.5, and the secondary soaking time is 3-10 min.

9. The preparation method according to claim 3 or 8, characterized in that: In S4, the adsorption time is 15-300 min.

10. The preparation method according to claim 3 or 8, characterized in that: In S4, The carbon nanotube conductive filler is selected from at least one of carbon black, graphene, carbon nanotubes and carbon nanosheets; The content of carbon nanotube conductive filler in the dispersion is 10-30 g / L.